EXHIBITION DESIGN for Permeable Boundaries: Interiors- a Field of Possibilities - Lommerse, Marina; Smith, Dianne; Beeck, Sarah (John Curtin Gallery, 2010)
Research Background :: The researchers not only curated the exhibition but also were the designers of the installation. Permeable Boundaries. Interiors—a field of possibilities. The design, captured the outcomes of the research but also through the creative activity, enabled insights and the research findings to emerge. Initially the Discipline was conceptualised as a field (in Bourdieu’s terms) that emerges and evolves through the beliefs, practices, and outcomes of its members. As a result the design captured the nature of permeability—perspex insertions, the fluidity of the concepts captured in text and images, as well as the projected slides of graduates work from early and latter parts of their careers. Therefore, questions were explored such as: What is the nature of Interior Architecture? What is the significance of a Curtin IA degree in the professional life of the graduates?Research Contribution :: The exhibition contributed by portraying information, by analysing the career paths and experiences in terms of the concepts arising spatially and graphically, and the juxtaposition of the current and past trajectories that make up ‘the field’. In addition, the exhibition also provided opportunities for data collection from alumni and other visitors. The exhibition was conceived as action research, whereby six generic totems emerged from the data; they in turn intersected with three broader conceptual models of Community Engagement, Cultural Heritage, Social Sustainability/Social Justice. Thereby a major research contribution is there definition of the profession of IA in contemporary workplace and education arenas. The design involved the overall layout, the materials, spatial qualities as well as content.Research Significance ::The exhibition design and conceptualisation worked on a number of levels, both as a reflective process as well as a strategic forum. It was significant at a local level because it modelled the use of creative practice as a form of Interior Architecture research; at a Practice level it captured the particulars of local designers engaging with interior architecture attributes to mould other ways of working and conceptualising the key foci; and at a Discipline level, it reconceptualised how Interior Architecture operates and can be represented. The latter is relevant nationally and internationally.Proof of prestige and quality :: Held in a prestigious registered gallery, John Curtin Gallery Supported by the Vice Chancellor of Curtin University and Deputy VC Academic Installed in the Chancellery, CU as a long term exhibit Winner of PVC award as part of the Permeable Boundaries package